Synthesis and Characterization of Dimers with Azo and Salicylaldimine as Linking Group - Padmini Tamilenthi, V.; Sulochana, N. (Asian Journal of Chemistry, 2010)
In the present study, a series of Schiff's bases: 1a-1d; N,N'-bis-[2- hydroxy-5-(4'-n-decyloxy)phenylazobenzylidene]-4,4'-diamino diphenylmethane (DDMO-n) (n-alkoxy = decyloxy, undecyloxy, dodecyloxy, tetradecyloxy) and N,N'-bis-[2-hydroxy-5-(4'-n-decyloxy)- benzylidene]-4,4'-diamino diphenyl methane (16aldddm) homologues have been synthesized and characterized by IR, NMR spectroscopy and elemental analyses. The mesomorphic character of these compounds was mainly studied by using polarizing microscope equipped with a heating and cooling stage. Electrochemical reductions were studied by use of cyclic-voltammetric technique. These compounds gave one peak and are irreversible in nature in presence of tetra butyl ammonium bromide (TBAB) as supporting electrolyte. The electrochemical reductions of imines group were found to be diffusion controlled. All the compounds showed good biological results.